Analysis of the Effect of Quality of Goods and Services on Purchase Decisions in the Shopee Application (Case Study on Saen John Store Customers) - Ifrizah Ifrizah; I Made Sukrisna; Tyas Zunia Arifianti; Indi Djastuti (Budapest International Research and Critics University, 2022)
Society’s behavioral pattern in shopping has changed from offline to online. This Online shopping trend sparked the occurrence new business called eCommerce. Shopee is one of the eCommerce platforms in Indonesia, it gives the sellers facilities to sell their products easily. Shopee has some features that can help its users to choose and buy the product they want. It also gives new experiences in shopping moreover in fashion. One of the star sellers in the men’s fashion category is Saen John. They sell chino pants and casual shirts. This study aims to know what factors and reasons users or customers in deciding to buy Sean John’s products are viewed from five groups.This study uses qualitative research method dan respondents are chosen by purposive sampling method. The respondents in this study are Saen John’s customers who bought twice or more. These customers are in A, B, C, D, and E groups. This study obtains 15 respondents from all groups using the semi-structured interview method. The results of this study found many factors that influence respondents to buy and use Saen John’s products. There are interesting reasons related to buying and using Sean John’s products according to the respondents such as quality, response, and service from the seller which are the consideration of customers.